COOKING DEMO OF BALANCED NUTRITIONAL MEALS FROM LOCAL FOOD INGREDIENTS IN INCREASING COMMUNITY KNOWLEDGE AND SKILLS THROUGH ASSISTANCE METHODS IN STUNTING LOCUS, MUARA ENIM DISTRICT - ., Susyani; ., Sartono; Sadiq, Ahmad; Telisa, Imelda; ., Terati; Kartika Sary, Devi; Friantini, Tri; Hasyim, Hamzah (LPPM Univ. Ibn Khaldun Bogor, 2023)
Muara Enim Regency is one of 17 districts in South Sumatra which is included in the category of high prevalence of stunting. The 2018 Riskesdas showed that the prevalence of stunting in Muara Enim was 34.4% higher than in South Sumatra (32%) and the National (30.8%). The same thing comes from the results of the 2021 national under-five nutritional status study, Muara Enim's stunting prevalence rate of 29.7% is included in the 3rd highest district in South Sumatra (24.8%). Research conducted by Susyani, et al (2022) in the stunting locus area of ​ Muara Enim Regency showed that 26 (9.6%) children under five were very short and 64 (23.5%) were short. The service aims to increase the knowledge and skills of mothers under five, women of childbearing age, and pregnant women in making balanced nutritious food by utilizing existing local food ingredients. The implementation method is carried out through nutrition education in the form of counseling and cooking demonstrations regarding nutritious and balanced food according to the contents of “ my plate”. There was an increase in knowledge about balanced nutritious food before and after being given counseling with an increase of 19.09 points. Demonstrations on cooking balanced nutritious food for toddler mothers, women of childbearing age, and pregnant women by utilizing existing local food ingredients can provide knowledge and skills of the target community in making various nutritious and balanced food menus to meet the nutritional needs of their families.